A fuel-limited isothermal DNA machine for the sensitive detection of cellular deoxyribonucleoside triphosphates. Issue 80 (16th September 2016) - Dong, Jiantong; Wu, Tongbo; Xiao, Yu; Xu, Lei; Fang, Simin; Zhao, Meiping
Abstract : A fuel-limited isothermal DNA machine has been built for the fluorescence detection of cellular deoxyribonucleoside triphosphates (dNTPs) at the fmol level. Abstract : A fuel-limited isothermal DNA machine has been built for the sensitive fluorescence detection of cellular deoxyribonucleoside triphosphates (dNTPs) at the fmol level, which greatly reduces the required sample cell number. Upon the input of the limiting target dNTP, the machine runs automatically at 37 °C without the need for higher temperature.